Туристи приступају еколошким хотелима и зелене хотелске преференције - AKSOZ, Emre Ozan; AYDIN, BİRGÜL and Yücel, Esin (Turizam, 2021)
The aim of this study is to determine how eco-friendly applications have an impact on the purchasing behaviour of tourists and hotel preferences.There are three aims of this study (1) to determine tourists approach the idea of accommodation in eco-friendly hotels (2) to determine tourists approach services in eco-friendly hotels and (3) to determine the opinions of tourists on choosing environmentally friendly hotels. The questionnaire was used as a data collection tool in the research. 408 participants included in the researched were surveyed. The majority of the tourists are sensitive about the environment by taking into account eco-friendly hotel accommodation preferences. The participants think that eco-friendly hotels are pioneer in developing new technologies, high qualified, happy to stay in eco-friendly hotels, and eco-friendly hotels evokes nature. Finally, the participants stated that eco-friendly hotels evokes health and wellness.